A three-year cohort study of the relationships between coping, job stress and burnout after a counselling intervention for help-seeking physicians - Hoffart Asle; Tyssen Reidar; Isaksson Ro Karin E; Sexton Harold; Aasland Olaf G; Gude Tore (BMC, 2010)
Abstract Background Knowledge about important factors in reduction of burnout is needed, but there is a dearth of burnout intervention program studies and their effects among physicians. The present three-year follow-up study aimed to investigate the roles of coping strategies, job stress and personality traits in burnout reduction after a counselling intervention for distressed physicians. Methods 227 physicians who attended a counselling intervention for burnout at the Resource Centre Villa Sana, Norway in 2003-2005, were followed with self-report assessments at baseline, one-year, and three-year follow-up. Main outcome measures were emotional exhaustion (one dimension of burnout), job stress, coping strategies and neuroticism. Changes in these measures were analyzed with repeated measures ANOVA. Temporal relationships between changes were examined using structural modelling with cross-lagged and synchronous panel models. Results 184 physicians (81%, 83 men, 101 women) completed the three-year follow-up assessment. Significantly reduced levels of emotional exhaustion, job stress, and emotion-focused coping strategies from baseline to one year after the intervention, were maintained at three-year follow-up. Panel modelling indicated that changes in emotion-focused coping (z = 4.05, p < 0.001) and job stress (z = 3.16, p < 0.01) preceded changes in emotional exhaustion from baseline to three-year follow-up. A similar pattern was found from baseline to one-year follow-up. Conclusion A sequential relationship indicated that reduction in emotion-focused coping and in job stress preceded reduction in emotional exhaustion. As a consequence, coping strategies and job stress could be important foci in intervention programs that aim to reduce or prevent burnout in help-seeking physicians.